2015
DOI: 10.7567/jjap.54.051002
|View full text |Cite
|
Sign up to set email alerts
|

Self-compensation effect in Si-doped Al0.55Ga0.45N layers for deep ultraviolet applications

Abstract: The self-compensation effect in Si-doped Al 0.55 Ga 0.45 N layers was investigated using different SiH 4 /III ratios. The degree of compressive strain changed with SiH 4 flow rate during growth. With a low SiH 4 /III ratio of 2.46 ' 10 %6 , compressive strain was increased in comparison with the un-doped case. However, above this SiH 4 /III ratio, compressive strain decreased from ε xx = %5.07 ' 10 %3 to 4.28 ' 10 %3 when the ratio was increased to 4.1 ' 10 %5 . For higher SiH 4 /III ratios, the compressive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…1. [9][10][11][12][13][14][28][29][30][31][32][33][34][35][36] The lowest resistance of n-AlGaN with an AlN mole fraction of 62% was achieved in this study. The lowest resistivity value of the Al 0.62 Ga 0.38 N layer reached 6.6 × 10 −3 Ω cm at the Si concentration of 3.2 × 10 19 cm −3 .…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…1. [9][10][11][12][13][14][28][29][30][31][32][33][34][35][36] The lowest resistance of n-AlGaN with an AlN mole fraction of 62% was achieved in this study. The lowest resistivity value of the Al 0.62 Ga 0.38 N layer reached 6.6 × 10 −3 Ω cm at the Si concentration of 3.2 × 10 19 cm −3 .…”
mentioning
confidence: 86%
“…(Color online) Resistivity values as a function of the AlN mole fraction for n-AlGaN layers. The data reported from other studies are indicated as open symbols,[9][10][11][12][13][14][28][29][30][31][32][33][34][35][36] while our results are shown as red closed symbols.…”
mentioning
confidence: 89%
“…Figure 3 summarizes the AlN mole fraction dependence of the resistivity of n-type AlGaN layers, showing our results as well as those reported previously. [19][20][21][22][23][24][35][36][37][38][39][40][41][42][43] We have reported the lowest resistivity (6.6 × 10 −3 Ω cm) of n-type AlGaN layer with x ∼ 0.62 at [Si] = 3.2 × 10 19 cm −3 . 30) We confirmed that this resistivity value allowed no visible resistance loss at the ntype AlGaN contact layer in the UV-LEDs.…”
Section: Decrease In Resistivity Of N-type Algan Contact Layer By Con...mentioning
confidence: 99%
“…3. (Color online) Reported resistivity values [19][20][21][22][23][24][35][36][37][38][39][40][41][42][43] for Si-doped Al x Ga 1−x N layers with various AlN mole fractions. We obtained one of the lowest resistivity values at x ∼ 0.62 by optimizing the growth conditions.…”
Section: Decrease In Resistivity Of N-type Algan Contact Layer By Con...mentioning
confidence: 99%
“…Aluminum nitride (AlN) based devices operating in the deep ultraviolet (UVC) regime (200–280 nm) have attracted considerable attention owing to their wide range of potential applications such as medical therapy, UV curing, biochemical sensing, water or air purification, and disinfection 1 3 . However, AlN based UVC devices still suffer from low quantum efficiency and output power.…”
Section: Introductionmentioning
confidence: 99%